ISOLASI DAN IDENTIFIKASI BAKTERI PSIKROTROFIK PEMBENTUK HISTAMIN DARI TUNA MATA BESAR - Rausan Fikri; Indun Dewi Puspita (Universitas Mataram, 2026)
This study aimed to isolate psychrotrophic histamine-forming bacteria (BPH) from bigeye tuna using Niven and EMB (eosine methylene blue) pre-screening media, and to identify the obtained BPH based on their biochemical and molecular characteristics. BPH were isolated from bigeye tuna that had been incubated at 16 oC for 5 days. Positive BPH isolates from Niven and EMB media were then grown in TSBH (trypticase soya broth histidine) medium at 5, 16, and 30 oC to test their activity in forming histamine using TLC (thin layer chromatography). Selected BPH were then identified biochemically and molecularly. BPH with high histamine-forming ability were obtained from Niven medium as many as 16 isolates (39.02%) and from EMB medium as many as 3 isolates (5.35%). The highest histamine-forming activity was obtained at 30 oC and then biochemical testing was carried out for all isolates at that temperature. Presumptive biochemical characterization of 19 isolates obtained 6 isolates that have different biochemical characteristics, namely oxidase, motility, ability to hydrolyze gelatin, and the ability to grow in 10% NaCl. The isolates came from Niven medium with codes TMB-N4, TMB-N9, TMB-N25, and TMB-N26 and from EMB medium with codes TMB-E38 and TMB-E40. The results of molecular testing for 6 isolates obtained the genus Morganella with a similarity percentage of >99% and biochemical characterization that leads to the species Morganella morganii subsp. sibonii. The acquisition of Morganella morganii subsp. sibonii bacteria from both EMB and Niven medium indicates that these bacteria are important organisms in the formation of histamine in fish that experience temperature abuse conditions during handling.